Integrated metric-ad hoc on-demand distance vector: a routing protocol over Wireless Mesh Networks - Rahman, Md. Arafatur; Anwar, Farhat; Azad, Md. Saiful (Science Publications, 2009)
Problem statement: Wireless Mesh Networks (WMNs) is an emerging technology for wireless environment. Since WMNs are permanent or semi-permanent network, an efficient and reliable path establishment is the core concern for such type of networks. Several performance metrics has been designed for WMNs such as Expected Transmission Count (ETX), Expected Transmission Time (ETT), interference Aware Routing Metric (iAWARE), Link Type Aware (LTA) Metric, Success Probability Product (SPP) and so on. However, each of these individual routing metric considered some selected features thus a single metric is inadequate for selecting the most reliable path. Consequently, it is necessary to integrate multiple performance metrics into a routing protocol to attain optimal performance. Approach: In this study we proposed a technique of integrating multiple metrics to improve the performance of a WMN routing protocol. This technique was implemented in Ad hoc On-Demand Distance Vector (AODV) routing protocol thus leading to the development of Integrated Metrics AODV (IM-AODV) routing protocol. Results: The simulation results indicated that IM-AODV protocol significantly outperformed the traditional AODV in WMNs environment. In a lightly loaded network the performance of IM-AODV is almost similar to AODV, however, in moderate to highly loaded network the performance of IM-AODV was improved by 10% (on average) compared to AODV. Conclusion/Recommendations: Incorporating multiple metrics in a routing protocol proved an effective mechanism for selecting the best path in a multi-hop wireless network (e.g. WMN) with loop free routing and avoiding highly loaded and lossy links. The proposed integrated metric scheme can also be considered for other routing protocols with simple modifications.